Bowel Preparation for Colonoscopy with Sodium Phosphate Solution versus Polyethylene Glycol-Based Lavage: A Multicenter Trial. (25th June 2008) - Schanz, S.; Kruis, W.; Mickisch, O.; Küppers, B.; Berg, P.; Frick, B.; Heiland, G.; Hüppe, D.; Schenck, B.; Horstkotte, H.; Winkler, A.
Abstract : Background : Adequate bowel preparation is essential for accurate colonoscopy. Both oral sodium phosphate (NaP) and polyethylene glycol-based lavage (PEG-ELS) are used predominantly as bowel cleansing modalities. NaP has gained popularity due to low drinking volume and lower costs. The purpose of this randomized multicenter observer blinded study was to compare three groups of cleansing (NaP, NaP + sennosides, PEG-ELS + sennosides) in reference to tolerability, acceptance, and cleanliness. Patient and Methods: 355 outpatients between 18 and 75 years were randomized into three groups (A, B, C) receiving NaP = A, NaP, and sennosides = B or PEG-ELS and sennosides = C. Gastroenterologists performing colonoscopies were blinded to the type of preparation. All patients documented tolerance and adverse events. Vital signs, premedication, completeness, discomfort, and complications were recorded. A quality score (0–4) of cleanliness was generated. Results : The three groups were similar with regard to age, sex, BMI, indication for colonoscopy, and comorbidity. Drinking volumes (L) (A = 4.33 + 1.2, B = 4.56 + 1.18, C = 4.93 + 1.71) were in favor of NaP (P = .005). Discomfort from ingested fluid was recorded in A = 39.8% (versus C:P = .015), B = 46.6% (versus C:P = .147), and C = 54.6%. Differences in tolerability and acceptance between the three groups were statistically not significant. No differences in adverse events and the cleanliness effects occurred in the three groups (P = .113). The cleanliness quality scores 0–2 were calculated in A: 77.7%, B: 86.7%, and C: 85.2%. Conclusions : These data fail to demonstrate significant differences in tolerability, acceptance, and preparation quality between the three types of bowel preparation for colonoscopy. Cleansing with NaP was not superior to PEG-ELS.